Linking the strike-slip kinematics of the Rennick Graben Fault system and the Aviator Fault from field structural data, North Victoria Land, Antarctica - Cianfarra, Paola; Salvini, Francesco; Crispini, Laura; Locatelli, Michele; Federico, Laura (2022)
The North Victoria Land structural framework is characterized by the long-lived tectonic activity along major crustal lineaments, including the NNW-SSE and NW-SE trending Rennick Graben Fault (RGF) system and Aviator Fault (AF). This tectonic corridor is characterized by an important strike-slip component that is easily connected to the main strike-slip fracture zone that characterizes the Southern Ocean between Australia and East-Antarctica. Structural analysis of field data along the RGF evidences a poly-phased activity with multiple reactivations related to the Paleozoic juxtaposition of NVL to the East Antarctic craton (as resulting from the Gondwana breakup) and to the Meso-Cenozoic plate tectonics associated to the Australia-East Antarctica separation and characterized by both offshore and onshore crustal strike-slip deformation. Both the northward, offshore propagation of the RGF system and its southward prosecution and link with the AF are inferred but still need to be proved/better framed. During the XXXVII Italian Antarctic campaign in the framework of the LARK project 92 field measurement sites have been surveyed between latitude 71.5°S and 73.5°S. To better frame the link between the RGF and AF the evidence of brittle deformation (including faults with the associated kinematic indicators and fracture attitude, dimension and sets) have been measured. This deformation involve rocks with ages ranging from Lower Paleozoic to Lower Jurassic. Where time constraints from stratigraphy are lacking and to better frame the age of the tectonics with its associated vertical displacement, ad hoc field samples have been collected for thermochronology dating. Open, un-mineralized fracture sets are important indicator of recent paleo-stress (tectonic) activity, since their formation is limited to shallow depth and their presence testify a short erosion time, thus representing a good indicator of the last, recent stress regime. The intensity of brittle deformation associated to this last tectonic setting can be ...